Factors and considerations for establishing and improving seasonal influenza vaccination of health workers: Report from a WHO meeting, January 16–17, Berlin, Germany. Issue 43 (8th October 2019) - ,; Al Awaidy, Salah; Bresee, Joseph S.; Chunsuttiwat, Supamit; Coulibaly, Daouda; Feng, Luzhao; Hale, Rachel; Madhi, Shabir; Maltezou, Helena C.; Moore, Kelly; Nguyen-Van-Tam, Jonathan; Omer, Saad; et al.
Abstract: Health workers represent an important target group for seasonal influenza vaccination because of their increased risk of infection as well as the risk of transmitting infection to vulnerable patients in the health care setting. Moreover, seasonal vaccination of health workers contributes to pandemic preparedness. However, many countries, especially in Africa and Asia, do not have policies for health worker influenza vaccination. In countries where such policies exist, vaccination coverage is often low. The World Health Organization (WHO) is developing a manual to guide the introduction of seasonal influenza vaccination of health workers. An Independent External Advisory Group (IEAG) that is advising WHO on the content of the manual met to discuss issues that are relevant and often unique to health worker vaccination. This meeting report summarizes the main issues that were discussed and the outcomes of the discussion. The issues include policy considerations, including the evidence in support of health worker vaccination; categorization and prioritization of health workers; the choice of vaccination strategy; its integration into broader health worker vaccination and occupational health policies; planning and management of vaccination, particularly the approaches for communication and demand generation; and the challenges with monitoring and evaluation of health worker vaccination, especially in low and middle-income countries.